Taming new physics in b → cūd(s) with τ(B +)/τ(B d ) and a sl d $$ {a}_{sl}^d $$ - Alexander Lenz; Jakob Müller; Maria Laura Piscopo; Aleksey V. Rusov (Journal of High Energy Physics, 2023)
Abstract Inspired by the recently observed tensions between the experimental data and the theoretical predictions, based on QCD factorisation, for several colour-allowed non-leptonic B-meson decays, we study the potential size of new physics (NP) effects in the decay channels b → cūd(s). Starting from the most general effective Hamiltonian describing the b → cūd(s) transitions, we compute NP contributions to the theoretical predictions of B-meson lifetime and of B-mixing observables. The well-known lifetime ratio τ(B +)/τ(B d ) and the experimental bound on the semi-leptonic CP asymmetry a sl d $$ {a}_{sl}^d $$ , provide strong, complementary constraints on some of the NP Wilson coefficients.